2022
DOI: 10.1038/s41598-021-03986-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors underpinning vaccine willingness in Israel, Japan and Hungary

Abstract: The spread of SARS-CoV-2 led to rapid vaccine development. However, there remains considerable vaccine hesitancy in some countries. We investigate vaccine willingness in three nations with very different vaccine histories: Israel, Japan and Hungary. Employing an ecological-systems approach we analyse associations between health status, individual cognitions, norms, trust in government, COVID-19 myths and willingness to be vaccinated, with data from three nationally representative samples (Israel, Jan. 2021, N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 37 publications
4
38
2
2
Order By: Relevance
“…Unfortunately, fear of unknown long-term side effects (Poland—41.1% of the respondents [ 30 ]), side effects (Russia—59.8% [ 31 ]; Poland—48.4% [ 30 ]; Czech Republic [ 32 ]), and anaphylaxis or other serious allergic reaction (Poland—33.2% [ 30 ]) due to insufficient and inappropriate scientific studies (Poland—[ 33 ]) and concerns about the effectiveness or safety (Russia—61.5% [ 31 ]; Romania—40% [ 34 , 35 ]; Czech Republic [ 32 ]) of the COVID-19 vaccine [ 19 ] threatened the “safety” level from Maslow’s pyramid [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Confidence In Vaccines’ Safety and Efficacymentioning
confidence: 99%
“…Unfortunately, fear of unknown long-term side effects (Poland—41.1% of the respondents [ 30 ]), side effects (Russia—59.8% [ 31 ]; Poland—48.4% [ 30 ]; Czech Republic [ 32 ]), and anaphylaxis or other serious allergic reaction (Poland—33.2% [ 30 ]) due to insufficient and inappropriate scientific studies (Poland—[ 33 ]) and concerns about the effectiveness or safety (Russia—61.5% [ 31 ]; Romania—40% [ 34 , 35 ]; Czech Republic [ 32 ]) of the COVID-19 vaccine [ 19 ] threatened the “safety” level from Maslow’s pyramid [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Confidence In Vaccines’ Safety and Efficacymentioning
confidence: 99%
“…Secondly, while our results can inform messaging techniques, we are not testing the impact of any particular messaging approach per se. Thirdly, while our study design includes a wide range of potential reasons for vaccine willingness, the list could be expanded even further to include, for example, measures of cultural myths [ 76 ] and beliefs about the safety [ 77 ] and provenience of the vaccine [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multi-country surveys have shown wide country-tocountry variation in vaccine acceptance (31-89%). 6,7 Systematic reviews of vaccine intention have found that various socioeconomic variables such as gender, age, race/ethnicity, education, income, and place of residence are associated with COVID-19 vaccine hesitancy. 8,9 Prior influenza vaccine history, trust in governmental institutions, compliance with subjective norms, and other behaviors and psychologic dispositions have also been shown to be associated with vaccine intention.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Prior influenza vaccine history, trust in governmental institutions, compliance with subjective norms, and other behaviors and psychologic dispositions have also been shown to be associated with vaccine intention. 7,10,11 Concerningly, the rate of vaccine hesitancy seems to have increased as the pandemic has progressed. 9 A multi-country analysis of vaccine confidence in 149 countries ranked Japan as among the countries with the lowest vaccine confidence in the world.…”
Section: Introductionmentioning
confidence: 99%